Effect of Aerobic Exercise on Liver Tissue in Rats with NAFLD. (10th September 2022) - Li, Li; Liu, Ruichen; Niu, Mengfan; Zhou, Tongxi
Abstract : Objective . To observe the improvement effect of aerobic exercise on liver tissue of rats with NAFLD, explore whether it can reduce NAFLD symptoms without drug dependence, and provide certain data support for the relief of NAFLD by aerobic exercise. Methods . 40 healthful male SD rats have been divided into ordinary diet and high-fat diet. To observe whether the molding is forming after 6 weeks, then divide the rats into control (C), model (M), and exercise (E) group. E group received 8-week aerobic exercise intervention. Serum and liver samples were taken and analyzed after the last intervention. Results . The morphological of hepatocytes between C and M group becomes different, and the accumulation of fat and inflammatory cells was significant, suggesting that NAFLD symptoms appeared, that is, the model was successfully established. Compared with M group, the morphology of rats in E group was improved in varying degrees. The quantity of ALT, AST, and MDA of rats in M group is increased, and the SOD activity is significantly reduced (P < 0.01 ). However, aerobic exercise intervention changed those result (P < 0.01 ). Conclusions . Aerobic exercise can relieve oxidative stress damage, lipid peroxidation levels, and chronic inflammatory status in rats with NAFLD, which can reduce NAFLD symptoms without drug dependence, and is expected to become a means of NAFLD treatment.